Mass Customization Capabilities in Practice – Introducing the Mass into Customized Tech-Textiles in an SME Network - Korneeva, Ekaterina; Hönigsberg, Sarah; Piller, Frank T. (International Journal of Industrial Engineering and Management, 2021)
The German textile industry is dominated by small and medium-sized enterprises (SMEs) with limited resources and specialized skills producing customized technical textiles following an engineer-to-order approach. To expand their skills, SMEs form business networks. The development and production of customized technical textile in networks are highly complex. The coordination requires high effort and results in inefficient and ineffective information flow, weakening the networks’ competitive advantage. Following a case study approach, we accompany an SME network over three years as they develop and implement a digital collaboration platform. We derived a framework of micro-foundations of Mass Customization capabilities supporting high-order Mass Customization capabilities for customer integration, solution space development, and robust processes. Thus, we present results on how an SME network in the textile industry leverages Mass Customization capabilities to increase efficiency via a digital collaboration platform. Article history: Received (January 11, 2021); Revised (April 2, 2021); Accepted (April 5, 2021); Published online (May 13, 2021)